A visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene and preparation method thereof

By combining Ulva biomass graphene with dysprosium oxide and nitrogen-deficient graphite phase carbon nitride, the prepared GO/Dy2O3/ND-g-C3N4 hydrogen production catalyst solves the problem of low efficiency in visible light response in the prior art, and achieves efficient photocatalytic hydrogen production effect.

CN116889881BActive Publication Date: 2025-03-18SHANDONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310670585.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-03-18
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

The existing semiconductor photocatalysts have low efficiency in visible light response, large bandwidth of band-discharge, and high electron-hole pair recombination rate, resulting in a small absorption range of visible light and a low effective charge separation rate, which limits their application in photocatalytic hydrogen production.

Method used

The GO/Dy2O3/ND-g-C3N4 hydrogen production catalyst was prepared by combining Ulva biomass graphene (GO), dysprosium oxide (Dy2O3) and nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4), and the GO/Dy2O3/ND-g-C3N4 hydrogen production catalyst was prepared by one-step synthesis through microwave hydrothermal reaction to improve the photocatalytic activity of the catalyst.

Benefits of technology

The visible light response capability and photocatalytic hydrogen production efficiency of the catalyst are significantly improved, and the hydrogen production rate reaches 560μmol·h-1·g-1 or above. Especially when the GO mass fraction is 6%, the hydrogen production rate is the highest, reaching about 760μmol·h-1·g-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116889881B_ABST
    Figure CN116889881B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of semiconductor photocatalysts, and specifically relates to a visible light responsive hydrogen production catalyst prepared from graphene-like enteromorpha biomass and a preparation method thereof. The catalyst includes GO with a mass fraction of 2 to 10%, and also includes dysprosium oxide and carbon nitride with nitrogen-defective graphite phase. The preparation method uses enteromorpha to prepare GO, and then obtains GO / Dy2O3 / ND‑g‑C3N4 catalyst by microwave hydrothermal reaction with prepared Dy2O3 / ND‑g‑C3N4. In the prepared catalyst, ND‑g‑C3N4 and GO act synergistically, so that the visible light responsive hydrogen production catalyst GO / Dy2O3 / ND‑g‑C3N4 has a higher photocatalytic hydrogen production efficiency than pure Dy2O3 itself and Dy2O3 / ND‑g‑C3N4 photocatalyst, especially when the mass fraction of GO is 6%, the hydrogen production rate is the highest.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor photocatalysts, and in particular relates to a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene and a preparation method thereof. Background Art

[0002] Enteromorpha is widely distributed in the coastal waters of various coastal countries, and has been increasing in recent years. In fact, enteromorpha can be converted into biomass oil, enteromorpha can be made into bio-crude oil, and bio-crude oil can be separated and refined to obtain gasoline and diesel. This makes enteromorpha a raw material for manufacturing new energy, and the development and research of new applications of enteromorpha cleared from the coastal waters has also become a hot topic in academic research.

[0003] Due to the acceleration of urbanization and industrialization, energy shortage and environmental pollution are becoming increasingly serious. Hydrogen energy, as a clean energy with high calorific value, is considered to be the most ideal alternative to traditional fossil fuels. Using solar energy to decompose water to produce hydrogen is a low-cost, high-efficiency and promising method for hydrogen production. Since 43% of sunlight is in the visible light region, the research on water decomposition under visible light irradiation has certain practical significance.

[0004] The key to producing hydrogen by splitting water under visible light is to construct an efficient and stable photocatalyst. So far, various catalysts for photocatalytic hydrogen evolution have been explored, such as semiconductor photocatalysts such as titanium dioxide (TiO2), zinc oxide (ZnO), cadmium sulfide (CdS), and graphite carbon nitride (g-C3N4). However, these single semiconductor photocatalysts usually have problems such as large bandgap width and high electron-hole pair recombination rate, which makes their light absorption range small and the effective charge separation rate low, thus not having high visible light catalytic hydrogen production ability. The unpaired electrons in the inner 4f orbit of dysprosium oxide (Dy2O3) give it an electronic energy level, and the f shell captures excited electrons during visible light irradiation, further delaying the recombination process of electron-hole pairs. However, the photocatalytic activity of Dy2O3 is not high, mainly because of its large bandgap width, which can only absorb ultraviolet light, which accounts for only about 4% of sunlight, and has poor response to visible light, which greatly limits the research and development of dysprosium oxide in photocatalytic hydrogen production. Based on the above shortcomings, in order to improve the visible light catalytic efficiency of Dy2O3, the use of narrow bandgap semiconductor coupling to form a heterojunction and the use of co-catalysts for modification are commonly used solutions.

[0005] Enteromorpha is bright green, has strong photosynthesis absorption, and is rich in carbon. There is relatively little research on the use of Enteromorpha and existing hydrogen production catalysts to prepare a new composite catalyst, which has become an urgent problem to be solved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene and a preparation method thereof, wherein enteromorpha biomass graphene (GO) is prepared using carbon powder prepared from enteromorpha, and then GO / Dy2O3 / ND-g-C3N4 hydrogen production catalyst with visible light response is prepared with nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4) and dysprosium oxide (Dy2O3), and the hydrogen production catalyst is applied to photolysis of water, and the hydrogen production rate is 560 μmol·h -1 ·g -1 The technical solution adopted is:

[0007] A visible light responsive hydrogen production catalyst prepared from enteromorpha biomass-like graphene comprises enteromorpha biomass-like graphene (GO) with a mass percentage of 2 to 10%, and also comprises dysprosium oxide (Dy2O3) and nitrogen-deficient graphite phase carbon nitride (ND-g-C3N4); wherein the mass ratio of nitrogen-deficient graphite phase carbon nitride to dysprosium oxide is 1:2 to 5, and the catalyst is an enteromorpha biomass-like graphene / dysprosium oxide / nitrogen-deficient graphite phase carbon nitride (GO / Dy2O3 / ND-g-C3N4) hydrogen production catalyst.

[0008] The method for preparing the above-mentioned visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene comprises the following steps:

[0009] (1) Carbonization of Enteromorpha biomass: The collected Enteromorpha was washed with distilled water to remove the sand and impurities therein, and then dried in an oven. The dried Enteromorpha was crushed with a grinder and passed through a 200-mesh sieve, and then placed in a tubular furnace and calcined under nitrogen flow, and then naturally cooled to room temperature to obtain Enteromorpha charcoal powder;

[0010] (2) Preparation of Enteromorpha biomass graphene (GO): The Enteromorpha charcoal powder obtained in step (1) was mixed with anhydrous potassium carbonate, ground in a mortar for 20 min, and then the mixture was transferred to a tube furnace and calcined under nitrogen. After naturally cooling to room temperature, the mixture was washed with deionized water to pH = 7, and then an appropriate amount of 1 mol / L dilute hydrochloric acid solution was added. After stirring for 2 h, the mixture was washed with deionized water to pH = 7, and vacuum dried to obtain GO;

[0011] (3) Preparation of graphite phase carbon nitride with nitrogen defects: modifying graphite phase carbon nitride (g-C3N4), dissolving urea in 50 mL of KOH aqueous solution, and drying in an oven; transferring the dried mixture to a crucible, calcining in a muffle furnace, cooling to room temperature naturally, washing with anhydrous ethanol and deionized water three times respectively, and placing in a vacuum drying oven to obtain graphite phase carbon nitride with nitrogen defects (ND-g-C3N4);

[0012] (4) Preparation of dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride (Dy2O3 / ND-g-C3N4): Place the nitrogen-deficient graphite-phase carbon nitride prepared in step (3) in 50 mL of deionized water, and disperse it evenly by ultrasonication to obtain a nitrogen-deficient graphite-phase carbon nitride suspension; Add dysprosium oxide to the nitrogen-deficient graphite-phase carbon nitride suspension, stir it evenly by ultrasonication, place it in a vacuum drying oven, transfer the obtained solid material to a porcelain boat, and calcine it in a tubular furnace to obtain Dy2O3 / ND-g-C3N4;

[0013] (5) GO suspension: placing the GO prepared in step (2) in deionized water and ultrasonically dispersing it to obtain a Enteromorpha biomass graphene suspension;

[0014] (6) mixing: adding dysprosium oxide / nitrogen-deficient graphite phase carbon nitride to the GO suspension prepared in step (5), and mixing by ultrasonic stirring to make it uniform;

[0015] (7) Preparing the hydrogen production catalyst by microwave hydrothermal reaction: The solution obtained in step (6) is transferred to a reactor, subjected to microwave hydrothermal reaction at a certain temperature for a period of time, then washed with deionized water, and dried in an oven at 60° C. to obtain the hydrogen production catalyst, namely GO / Dy2O3 / ND-g-C3N4.

[0016] Preferably, in step (1), the drying temperature is 105° C., the heating rate of the tubular furnace is 5° C. / min, the roasting temperature is 600° C., and the roasting time is 2 h.

[0017] Preferably, in step (2), the mass ratio of enteromorpha charcoal powder to anhydrous potassium carbonate is 1:2-4; the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 800°C, the roasting time is 2h, and the vacuum drying temperature is 60°C.

[0018] Preferably, in step (3), the mass ratio of urea to KOH is 100-150:1, the drying temperature is 60°C, the roasting temperature is 550°C, the roasting time is 3h, the heating rate is 5°C / min, and the temperature used for vacuum drying is 55°C.

[0019] Preferably, in step (4), the stirring time is 1 hour, the ultrasonic time is 1 hour, the vacuum drying temperature is 60°C, the tubular furnace heating rate is 5°C / min, the roasting temperature is 500°C, and the roasting time is 3 hours.

[0020] Preferably, in step (5), the ultrasonic stirring time is 2 hours to ensure uniform dispersion.

[0021] Preferably, in step (7), the microwave hydrothermal reaction time is 60 min, and the microwave hydrothermal reaction temperature is 80-160°C.

[0022] As a further preference, the microwave hydrothermal reaction temperature is 100°C.

[0023] Preferably, in the prepared hydrogen production catalyst, the mass percentage of enteromorpha biomass-based graphene is 6%.

[0024] Compared with the prior art, the present invention is beneficial in that:

[0025] In the present invention, the heterojunction formed by Dy2O3 and ND-g-C3N4 can promote the separation of photogenerated carriers, and the excited electrons in the conduction band (CB) of ND-g-C3N4 with a higher potential are transferred to the CB of Dy2O3 at a relatively low potential, and the photogenerated holes in the valence band (VB) of Dy2O3 with a higher potential can be transferred to the VB of ND-g-C3N4 with a lower potential. GO has a large surface area and good electron transfer ability, which can improve the photocatalytic activity. More importantly, ND-g-C3N4 and GO have a synergistic effect, so that the visible light responsive hydrogen production catalyst GO / Dy2O3 / ND-g-C3N4 has a higher photocatalytic hydrogen production efficiency than pure Dy2O3 itself and Dy2O3 / ND-g-C3N4 photocatalyst, especially when the mass fraction of GO is 6%, the hydrogen production rate is the highest, which can reach 760μmol·h -1 ·g -1 And the synthesis method is relatively simple and easy to operate, and can be synthesized in one step. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD spectra of the GO / Dy2O3 / ND-g-C3N4 catalyst prepared in the present invention that responds to visible light with changes in GO loading amount and pure Dy2O3 and Dy2O3 / ND-g-C3N4.

[0027] Figure 2 The XRD spectrum of the GO / Dy2O3 / ND-g-C3N4 catalyst prepared in the present invention that responds to visible light of the temperature change of the microwave hydrothermal reaction.

[0028] Figure 3 This is a scanning electron microscope image of GO / Dy2O3 / ND-g-C3N4 prepared in Example 3 of the present invention.

[0029] Figure 4 The UV-visible diffuse reflectance spectra of the visible light responsive GO / Dy2O3 / ND-g-C3N4 catalyst with changing GO loading prepared in the present invention and pure Dy2O3 and Dy2O3 / ND-g-C3N4 are shown.

[0030] Figure 5The figure is a UV-visible diffuse reflectance spectrum of the GO / Dy2O3 / ND-g-C3N4 catalyst that responds to visible light in response to the temperature change of the microwave hydrothermal reaction prepared by the present invention.

[0031] Figure 6 This is a graph of the hydrogen production efficiency of the visible light responsive hydrogen production photocatalyst GO / Dy2O3 / ND-g-C3N4 with varying GO loading prepared in the present invention and pure Dy2O3 and Dy2O3 / ND-g-C3N4 for 4h.

[0032] Figure 7 This is a graph of the hydrogen production efficiency of the GO / Dy2O3 / ND-g-C3N4 catalyst prepared in the present invention for 4 hours in response to visible light of the temperature change of the microwave hydrothermal reaction. DETAILED DESCRIPTION

[0033] The drawings are only used for illustrative purposes; for those skilled in the art, some well-known structures and their descriptions in the drawings may be omitted, and therefore, they should not be understood as limitations on the present invention.

[0034] The sources of the raw materials used in the present invention are not particularly limited and can be commercially available.

[0035] The technical solutions and effects of the present invention are described in detail below with reference to the accompanying drawings.

[0036] Example 1

[0037] A method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene, the method comprising the following steps:

[0038] (1) Carbonization of Enteromorpha biomass: The collected Enteromorpha was washed with distilled water to remove the sand and impurities, and then dried in an oven at a drying temperature of 105°C. The dried Enteromorpha was crushed with a pulverizer and passed through a 200-mesh sieve, then placed in a tubular furnace and calcined under nitrogen conditions. The heating rate of the tubular furnace was 5°C / min, the calcination temperature was 600°C, and the calcination time was 2h. After the calcination was completed, the Enteromorpha charcoal powder was obtained after the temperature was naturally cooled to room temperature.

[0039] (2) Preparation of Enteromorpha biomass graphene (GO): 0.1 g of Enteromorpha charcoal powder obtained in step (1) was mixed with 0.3 g of anhydrous potassium carbonate, ground in a mortar for 20 min, and then the mixture was transferred to a tube furnace and calcined under nitrogen. The heating rate of the tube furnace was 5 ° C / min, the calcination temperature was 800 ° C, and the calcination time was 2 h. After the calcination was completed, it was taken out, cooled naturally to room temperature, washed with deionized water to pH = 7, and then an appropriate amount of 1 mol / L dilute hydrochloric acid solution was added. After stirring for 2 h, it was washed with deionized water to pH = 7, and vacuum dried at a drying temperature of 60 ° C to obtain GO.

[0040] (3) Preparation of graphite carbon nitride with nitrogen defects (ND-g-C3N4): 7.5 g of urea was dissolved in 50 mL of KOH aqueous solution (the mass of KOH was 0.06 g), and the mixture was placed in an oven to dry at 60°C. The dried mixture was transferred to a crucible and calcined in a muffle furnace at 550°C for 3 h at a heating rate of 5°C / min. After calcination, the mixture was taken out and cooled to room temperature naturally. The mixture was then washed three times with anhydrous ethanol and deionized water respectively, and then placed in a vacuum drying oven at 55°C to obtain ND-g-C3N4.

[0041] (4) Preparation of dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride (Dy2O3 / ND-g-C3N4): Place 0.133 g of nitrogen-deficient graphite-phase carbon nitride prepared in step (3) in 50 mL of deionized water and disperse it evenly by ultrasonication to obtain a ND-g-C3N4 suspension; Add 0.4 g of dysprosium oxide (Dy2O3) to the ND-g-C3N4 suspension, stir it ultrasonically for 1 h to mix it evenly, place it in a vacuum drying oven at 60°C to dry, and then transfer the obtained solid material to a porcelain boat and calcine it in a tubular furnace at a heating rate of 5°C / min, a calcination temperature of 500°C, and a calcination time of 3 h to obtain Dy2O3 / ND-g-C3N4.

[0042] (5) GO suspension: The GO prepared in step (2) was placed in deionized water and ultrasonically stirred for 2 h to disperse it to obtain a GO suspension;

[0043] (6) mixing: adding dysprosium oxide / nitrogen-deficient graphite phase carbon nitride to the GO suspension prepared in step (5), and mixing by ultrasonic stirring to make it uniform;

[0044] (7) Preparation of the hydrogen production catalyst by microwave hydrothermal reaction: The solution obtained in step (6) was transferred to a reactor, reacted at 100° C. for 60 min, then washed with deionized water for 3 times, and then dried in an oven at 60° C. to obtain the hydrogen production catalyst, namely GO / Dy2O3 / ND-g-C3N4, see Figure 3 SEM images shown.

[0045] In the prepared GO / Dy2O3 / ND-g-C3N4 catalyst, the mass percentage of GO is 2%, and the prepared catalyst is marked as 2% GO-Dy2O3-CN. In the specification and drawings of the present invention, CN is used to represent ND-g-C3N4.

[0046] Example 2

[0047] In the prepared GO / Dy2O3 / ND-g-C3N4 catalyst, the mass percentage of GO is 4%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 4% GO-Dy2O3-CN.

[0048] Example 3

[0049] In the prepared GO / Dy2O3 / ND-g-C3N4 catalyst, the mass percentage of GO is 6%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 6% GO-Dy2O3-CN (because the temperature of the microwave hydrothermal reaction is 100°C, it is also marked as 6% GO-Dy2O3-CN, 100°C), see Figure 3 shown.

[0050] Example 4

[0051] In the prepared GO / Dy2O3 / ND-g-C3N4 catalyst, the mass percentage of GO is 8%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 8% GO-Dy2O3-CN.

[0052] Example 5

[0053] In the prepared GO / Dy2O3 / ND-g-C3N4 catalyst, the mass percentage of GO is 10%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 10% GO-Dy2O3-CN.

[0054] Example 6

[0055] In the step (7), the temperature of the microwave hydrothermal reaction is 80°C, the mass percentage of GO in the GO / Dy2O3 / ND-g-C3N4 catalyst is 6%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 6% GO-Dy2O3-CN, 80°C.

[0056] Example 7

[0057] In the step (7), the temperature of the microwave hydrothermal reaction is 120°C, the mass percentage of GO in the GO / Dy2O3 / ND-g-C3N4 catalyst is 6%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 6% GO-Dy2O3-CN, 120°C.

[0058] Example 8

[0059] In the step (7), the temperature of the microwave hydrothermal reaction is 140°C, the mass percentage of GO in the GO / Dy2O3 / ND-g-C3N4 catalyst is 6%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 6% GO-Dy2O3-CN, 140°C.

[0060] Example 9

[0061] In the step (7), the temperature of the microwave hydrothermal reaction is 160°C, the mass percentage of GO in the GO / Dy2O3 / ND-g-C3N4 catalyst is 6%, and other details not mentioned are the same as those in Example 1. The prepared catalyst is marked as 6% GO-Dy2O3-CN, 160°C.

[0062] like Figure 1 As shown, in the composite sample (i.e. the prepared catalyst, the composite material also refers to the prepared catalyst, the same below), Dy2O3 has characteristic peaks at 2θ=20.32°, 29.04°, 33.64°, 43.25°, 48.36°, and 57.32°, which correspond to the (211), (222), (400), (134), (400), and (622) crystal planes of cubic phase Dy2O3 (JCPDS card: No.78-0388), respectively. The characteristic peak of ND-g-C3N4 at 2θ=27.21° corresponds to the (002) crystal plane of graphite phase carbon nitride (JCPDS card: No.87-1526). No characteristic peak of GO was observed in the composite sample, which is due to the low doping amount of GO and the high dispersion of GO. Compared with pure Dy2O3 and binary composite samples, the position and quantity of characteristic peaks of the composite samples did not change significantly after loading with GO, indicating that the introduction of GO will not change the crystal structure of Dy2O3.

[0063] like Figure 2 As shown in the figure, after determining the optimal conditions when GO loading is used as a single factor, the microwave hydrothermal temperature is used as a single factor to explore the effect of temperature on the crystal structure of the composite photocatalyst. XRD characterization was performed on the GO / Dy2O3 / ND-g-C3N4 composite photocatalyst prepared under different microwave hydrothermal temperature conditions. When the microwave hydrothermal temperature is 80-160℃, the characteristic peak of Dy2O3 in the composite sample is sharper and there are no other impurity peaks, indicating that ND-g-C3N4 will not destroy the crystal structure during the composite process, and the prepared composite sample has a high purity. When the microwave hydrothermal temperature is 100℃, the intensity of the characteristic peak of the composite is enhanced to the greatest extent, indicating that there is an optimal microwave hydrothermal temperature range in the sample preparation process. Good crystallization will reduce the defects of semiconductor photocatalysis, facilitate the transfer of photogenerated carriers within and between the lattices, and thus improve the activity of photocatalysis.

[0064] like Figure 3 As shown in the SEM image of the composite sample, it can be seen that ND-g-C3N4 is evenly dispersed between Dy2O3, but the original rod-like structure of Dy2O3 is not destroyed. GO as a carrier can not only increase the specific surface area of ​​the sample, but also accelerate the separation and transfer speed of carriers. At the same time, the three substances are closely distributed, indicating that the GO / Dy2O3 / ND-g-C3N4 composite sample was successfully synthesized.

[0065] like Figure 4 As shown in the UV-visible diffuse reflectance spectrum of Dy2O3, it can be seen that Dy2O3 has absorption peaks at 349nm, 363nm, 385nm, 424nm, 450nm, and 473nm, in addition to the absorption peak at 230nm, corresponding to 6H 15 / 2 Ground state to 6P 7 / 2 , 6P 5 / 2 , 4F 7 / 2 +4I 13 / 2 , 4G 11 / 2 , 4I 15 / 2 , 4F 9 / 2 Compared with pure Dy2O3 and binary composite samples, the absorption peak of the composite sample red-shifts after loading with GO, which shows that the introduction of GO improves the visible light response range of the system.

[0066] like Figure 5 As shown, different microwave hydrothermal temperatures will also affect the light absorption capacity of the composite sample. Among them, the light response ability of the composite sample prepared when the GO loading amount is 6% and the microwave hydrothermal temperature is 100°C is most significantly improved.

[0067] like Figure 6 As shown in the figure, compared with pure Dy2O3 and binary composite samples, the hydrogen production rate of the composite sample increased after loading GO. This shows that loading GO can effectively increase the separation rate of photogenerated carriers and improve the photocatalytic hydrogen production performance of Dy2O3. The loading amount of GO has a great influence on the hydrogen production rate of the composite photocatalyst. With the increase of GO loading, the hydrogen production rate of the composite photocatalyst first increased and then decreased, reaching the maximum value at a loading amount of 6%, indicating that excessive GO covers the surface of Dy2O3, blocking part of the visible light and reducing the reaction active sites.

[0068] like Figure 7 As shown in Figure 2, the average hydrogen production rate of the composite samples prepared under different microwave hydrothermal temperature conditions was 700 μmol·g -1 ·h -1When the microwave hydrothermal temperature is 100°C, the hydrogen production rate reaches the maximum value, and when the microwave hydrothermal temperature is higher than 100°C, the hydrogen production rate decreases rapidly. According to the results of the composite sample characterization experiment, if the preparation temperature of the composite sample is too high, it will greatly affect its crystal growth. Good crystallization will reduce the defects of semiconductor photocatalysis and facilitate the transfer of photogenerated carriers within and between the lattices, thereby improving the activity of photocatalysis.

[0069] Of course, the description of the above specific embodiments is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene, characterized in that: The catalyst includes 2-10% by mass of Enteromorpha biomass-based graphene, and also includes dysprosium oxide and graphite phase carbon nitride with nitrogen defects; wherein the mass ratio of the graphite phase carbon nitride with nitrogen defects to dysprosium oxide is 1:2-5, and the catalyst is an Enteromorpha biomass-based graphene / dysprosium oxide / graphite phase carbon nitride with nitrogen defects hydrogen production catalyst; The method comprises the following steps: (1) Carbonization of Enteromorpha biomass: The collected Enteromorpha was washed with distilled water to remove the sand and impurities therein, and then dried in an oven. The dried Enteromorpha was crushed with a grinder and passed through a 200-mesh sieve, and then placed in a tubular furnace and calcined under nitrogen flow, and then naturally cooled to room temperature to obtain Enteromorpha charcoal powder; (2) Preparation of Enteromorpha biomass-based graphene: The Enteromorpha charcoal powder obtained in step (1) was mixed with anhydrous potassium carbonate, ground in a mortar for 20 min, and then the mixture was transferred to a tube furnace, calcined under nitrogen, cooled naturally to room temperature, washed with deionized water to pH = 7, and then added with an appropriate amount of 1 mol / L dilute hydrochloric acid solution. After stirring for 2 h, the mixture was washed with deionized water to pH = 7, and vacuum dried to obtain Enteromorpha biomass-based graphene; (3) Preparation of graphite phase carbon nitride with nitrogen defects: urea was dissolved in 50 mL of KOH aqueous solution and dried in an oven; the dried mixture was transferred to a crucible, calcined in a muffle furnace, cooled to room temperature naturally, washed three times with anhydrous ethanol and deionized water respectively, and placed in a vacuum drying oven to obtain graphite phase carbon nitride with nitrogen defects; (4) Preparing dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride: placing the nitrogen-deficient graphite-phase carbon nitride prepared in step (3) in 50 mL of deionized water, and uniformly dispersing it by ultrasonication to obtain a graphite-phase carbon nitride suspension having nitrogen defects; adding dysprosium oxide to the nitrogen-deficient graphite-phase carbon nitride suspension, and uniformly mixing it by ultrasonication, placing it in a vacuum drying oven, and transferring the obtained solid material to a porcelain boat, and calcining it in a tubular furnace to obtain dysprosium oxide / nitrogen-deficient graphite-phase carbon nitride; (5) Enteromorpha biomass-based graphene suspension: placing the Enteromorpha biomass-based graphene prepared in step (2) in deionized water and dispersing it by ultrasonication to obtain an Enteromorpha biomass-based graphene suspension; (6) Mixing: adding dysprosium oxide / nitrogen-deficient graphite phase carbon nitride to the Enteromorpha biomass graphene suspension prepared in step (5), and mixing by ultrasonic stirring to make the mixture uniform; (7) Preparing the hydrogen production catalyst by microwave hydrothermal reaction: The solution obtained in step (6) is transferred to a reactor, subjected to microwave hydrothermal reaction at a certain temperature for a period of time, then washed with deionized water, and dried in an oven at 60° C. to obtain the hydrogen production catalyst.

2. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (1), the drying temperature is 105°C, the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 600°C, and the roasting time is 2h.

3. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (2), the mass ratio of enteromorpha charcoal powder to anhydrous potassium carbonate is 1:2-4; the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 800°C, the roasting time is 2h, and the vacuum drying temperature is 60°C.

4. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (3), the mass ratio of urea to KOH is 100-150:1, the drying temperature is 60°C, the roasting temperature is 550°C, the roasting time is 3h, the heating rate is 5°C / min, and the temperature used for vacuum drying is 55°C.

5. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (4), the stirring time is 1 hour, the ultrasonic time is 1 hour, the vacuum drying temperature is 60°C, the tubular furnace heating rate is 5°C / min, the roasting temperature is 500°C, and the roasting time is 3 hours.

6. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (5), the ultrasonic stirring time is 2 hours to ensure uniform dispersion.

7. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the step (7), the microwave hydrothermal reaction time is 60 min, and the microwave hydrothermal reaction temperature is 80-160° C.

8. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 7, characterized in that: The microwave hydrothermal reaction temperature was 100 °C.

9. The method for preparing a visible light responsive hydrogen production catalyst prepared from enteromorpha biomass graphene according to claim 1, characterized in that: In the prepared hydrogen production catalyst, the mass percentage of enteromorpha biomass-like graphene is 6%.

Citation Information

Patent Citations

  • Preparation method of S-graphite phase carbon nitride and graphene oxide photocatalyst

    CN114367300A